BAHASA INDONESIA PADA RUBRIK ESAI MEDIA ONLINE MOJOK DAN PENGGUNAANNYA DALAM PEMBELAJARAN MENULIS ARTIKEL DI SEKOLAH MENENGAH ATAS - Alfi Nur Janah; Budhi Setiawan; Kundharu Saddhono (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims are: (1) to describe the relation of the title to the content; (2) to describe the organization of languages related to cohesion and coherence; (3) to describe sentence effectiveness; (4) to describe accuracy of diction usage; (5) to describe the correct use of spelling and punctuation; (6) to describe the relevance of the use of Indonesian language in Essay rubric of Mojok online media to learning writing articles in Senior High School. The method used is descriptive qualitative, Data sources used in the form of documents and informants. The sampling technique uses purposive sampling. Data collection technique using document analysis and interview techniques. Data validity is done by theory triangulation and source triangulation. Data analysis uses content analysis. The results of the study can be described as follows: (1) The structure of the essay in the title, introduction, content and closing has a good unity; (2) Organizing language related to cohesion and coherence is characterized by grammatical cohesion, lexical cohesion, and conjunction where lexical cohesion are the most widely used markers of essay writers; (3) The effectiveness of sentences is divided into three structures namely general sentence structure, parallel sentence structure, and periodic sentence structure that meets the requirements of unity, efficiency, emphasis, and variation which the structure of periodic sentences is the dominant sentence structure used in essay; (4) The correct use of diction is divided into special words, common words, expansion of meaning, narrowing of meaning, amelioration, correction, metaphor, and metonymy which is special words and common words is the most widely used by essay writers; (5) Accuracy in using spelling punctuation includes the use of letters, writing words, and using punctuation according to PUEBI, especially the use of capital letters and the use of periods; (6) The use of Indonesia language in the Essay Rubric of Mojok online media is relevant to write articles in senior high school.